Dampak Depresi Terhadap Intensitas Nyeri dan Disabilitas pada Pasien dengan Chronic Low Back Pain - Felicia, Ivana; Singh, Arwinder (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Introduction: Low back pain (LBP) is a common health issueexperienced by nearly 80% of people throughout their lives. Thiscondition often recurs and can become chronic low back pain (CLBP) ifit lasts for more than 3 months, with a prevalence of approximately 23%and causing disability in about 11-12% of the population. CLBP is oftenassociated with depression, which can worsen pain intensity, function,and patient recovery. Purpose: This study aims to analyze therelationship between depression and CLBP, as well as the factors thatinfluence it. Methods: The study uses a cross-sectional analyticalobservation method with consecutive sampling of 170 respondents. Datawere collected through interviews and questionnaires, including painintensity measurement using the Numeric Rating Scale, depression levelsusing the Beck Depression Inventory-II, and disability levels using theOswestry Disability Index. Data collection was conducted at SumberWaras Hospital and dr. Mintohardjo Naval Hospital. Results: The studyresults show the highest prevalence of LBP in individuals over 65 yearsold (47.65%), and the majority of respondents were female (70.59%).There is a significant relationship between pain intensity and depression(p < 0.001) and between disability and depression (p < 0.001). Painduration was not significantly associated with depression (p = 0.211).Conclusion: In conclusion, pain intensity and disability level aresignificantly associated with the incidence of depression in CLBPpatients.